The effect of hydroxychloroquine on platelet activation in model experiments - Schreiber, Karen; Sciascia, Savino; Wehrmann, Florian; Weiß, Christel; Leipe, Jan; Krämer, Bernhard; Stach-Jablonski, Ksenija (Journal of thrombosis and thrombolysis, 2021)
Hydroxychloroquine (HCQ) is an antimalarial agent with pleiotropic effects and now represents a cornerstone in the management of patients with autoimmune conditions. While clinical series suggest anti-thrombotic properties, the way in which HCQ exerts this effect remains to be fully explained. Following a 24-h incubation of human umbilical vein endothelial cells (HUVEC) and human umbilical arterial endothelial cells (HUAEC) with HCQ (concentration 500, 1000 and 2000 ng/ml), these cells were then stimulated for an hour with tumor necrosis factor alpha (TNF-α) and were subsequently incubated in direct contact with thrombin-activated platelets. The expression of CD40L on platelets was measured by flow cytometry. The expression of CD40L on platelets significantly increased after direct incubation with 1000 ng/ml and 2000 ng/ml concentrations of HCQ. In contrast, after pre-incubation of HUAECs with 1000 ng/ml HCQ and following stimulation with platelets the expression of CD40L was significantly reduced also after stimulation with thrombin and TNF-α activated platelets. It was shown that the expression of CD40L on the platelets was not significantly reduced by different HCQ concentrations after contact with HCQ pre-incubated HUVECs. HCQ reduces the stimulatory effect of thrombin and TNF-α on platelet activation in the presence of endothelial cells. Our experiments suggest that HCQ pre-incubated HUAEC cells result in a reduced platelets activation measured by means of CD40L expression. Further, our results show that direct HCQ incubation of platelets (without the presence of EC) increased the expression of CD40L suggesting that the observed effect of HCQ on platelet activation may be EC mediated.
Gesehen am 28.11.2022